2000
DOI: 10.1007/pl00010313
|View full text |Cite
|
Sign up to set email alerts
|

Polycationic Salts V [1]. 15N NMR Spectra of Amines, Ammonium Salt Monomers, and Polymers of Styrene Based Trialkylammonium Salts

Abstract: 15 N NMR spectroscopy was found to be essential for the detailed characterization of tertiary amines, vinylbenzylammonium salts, and polymers derived from these compounds. It proved important for the characterization of low 2-ionene oligomers and vinylbenzylammonium salts derived thereof as well. The polymers of these novel monomers were also characterized and identi®ed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…30 ppm relative to the free ligand 6. This is in line with a deshielded quaternary ammonium atom, 39,40 indicating that the nitrogen atom is coordinated to the metal center.…”
Section: ■ Introductionsupporting
confidence: 60%
“…30 ppm relative to the free ligand 6. This is in line with a deshielded quaternary ammonium atom, 39,40 indicating that the nitrogen atom is coordinated to the metal center.…”
Section: ■ Introductionsupporting
confidence: 60%
“…The identification of the 2‐ionene oligomers and side products was accomplished by 15 N NMR spectroscopy. 15 N enrichment of our 2‐ionene compounds was not necessary because of the high solubility of these compounds (O‐1, O‐2, and O‐3) in DI water (10.0 M) 38. TMED exhibits a single peak at −357.9 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, Olah and co‐workers found that the 17 O nuclei in oxonium ions are generally deshielded compared to those in their parent alcohols and ethers . For nitrogen (observed by 15 N NMR analysis), the result seems to depend on the situation; the nitrogen atom in protonated trimethylamine is deshielded relative to the free base, while the nitrogen atom in tetramethylammonium bromide is shielded relative to trimethylamine …”
Section: Methodsmentioning
confidence: 99%